Land‐use history exerts long‐term effects on the clear‐cut flora in boreonemoral Sweden. Issue 4 (10th May 2016) - Jonason, Dennis; Bergman, Karl‐Olof; Westerberg, Lars; Milberg, Per
Abstract: Questions: Can signs of 19th century grassland management, which can be observed in the flora immediately (2–4 yrs) after clear‐cutting in boreonemoral Sweden, still remain 4 yrs later? Do the effects from the time since clear‐cutting differ between forest and grassland plant species? Location: Province of Östergötland, southern Sweden. Methods: Twelve contemporary clear‐cut areas that were once meadows and 12 that were once forests were selected using land‐use maps from the 1870s. Grasses and herbaceous plants were surveyed twice, once in 2009 and once in 2013 (2–4 and 6–8 yrs after clear‐cutting, respectively). Plant presence was recorded within 100 circular sample plots (radius 1 m) placed evenly throughout each respective clear‐cut area along transects spaced 25‐m apart. The number of sample plots in which a species was present was taken as a measure of that species' frequency. Random effects meta‐analysis, odds ratios and ANCOVA were used to analyse species responses to clear‐cutting over time. Results: A total of 170 plant species were found in the study, of which 33 were classified as grassland indicator species and 31 as plants primarily confined to forests. Clear‐cut areas with a history as meadowland had, on average, up to 64% higher total species richness and 110% more grassland indicator species than did clear‐cut areas with a history as forest. The time since clear‐cutting had no effect on total species richness. However, the odds of finding a grassland indicator species decreased with the time since clear‐cutting, whereas the odds of finding a forest species increased. Conclusions: We concluded that land‐use history plays an important role in explaining the flora found in Swedish clear‐cuts, and that its effects on species richness remain for a minimum of 8 yrs after harvest (conservative estimate). This phenomenon highlights the importance of acknowledging land‐use legacies in ecological research and conservation. Future studies should investigate various options for the promotion of grassland plants in clear‐cuts with a history of grassland management while also acknowledging the potential conflicts between conservation and production. The results may pertain to other countries with similar land‐use histories. Abstract : Do signs of 19th century grassland management, known from the clear‐cut flora in Sweden, remain up to eight years later? The time since clear‐cutting had no effect on total species richness. However, the odds of finding a grassland indicator species decreased over time, but increased for forest species. We highlight land use legacies as important components in research and conservation.